Characterization of branched ultrahigh molar mass polymers by asymmetrical flow field-flow fractionation and size exclusion chromatography - Otte, Tino; Stadler, Florian; Kaschta, Joachim; Becker, Florian; Buback, Michael; et al. (Journal of Chromatography A, 2011)
The molar mass distribution (MMD) of synthetic polymers is frequently analyzed by size exclusion chromatography (SEC) coupled to multi angle light scattering (MALS) detection. For ultrahigh molar mass (UHM) or branched polymers this method is not sufficient, because shear degradation and abnormal elution effects falsify the calculated molar mass distribution and information on branching. High temperatures above 130 degrees C have to be applied for dissolution and separation of semi-crystalline materials like polyolefins which requires special hardware setups. Asymmetrical flow field-flow fractionation (AF4) offers the possibility to overcome some of the main problems of SEC due to the absence of an obstructing porous stationary phase. The SEC-separation mainly depends on the pore size distribution of the used column set. The analyte molecules can enter the pores of the stationary phase in dependence on their hydrodynamic volume. The archived separation is a result of the retention time of the analyte species inside SEC-column which depends on the accessibility of the pores, the residence time inside the pores and the diffusion ability of the analyte molecules. The elution order in SEC is typically from low to high hydrodynamic volume. On the contrary AF4 separates according to the diffusion coefficient of the analyte molecules as long as the chosen conditions support the normal FFF-separation mechanism. The separation takes place in an empty channel and is caused by a cross-flow field perpendicular to the solvent flow. The analyte molecules will arrange in different channel heights depending on the diffusion coefficients. The parabolic-shaped flow profile inside the channel leads to different elution velocities. The species with low hydrodynamic volume will elute first while the species with high hydrodynamic volume elute later. The AF4 can be performed at ambient or high temperature (AT-/HT-AF4). We have analyzed one low molar mass polyethylene sample and a number of narrow distributed polystyrene standards as reference materials with known structure by AT/HT-SEC and AT/HT-AF4. Low density polyethylenes as well as polypropylene and polybutadiene, containing high degrees of branching and high molar masses, have been analyzed with both methods. As in SEC the relationship between the radius of gyration (R(g)) or the molar mass and the elution volume is curved up towards high elution volumes, a correct calculation of the MMD and the molar mass average or branching ratio is not possible using the data from the SEC measurements. In contrast to SEC. AF4 allows the precise determination of the MMD, the molar mass averages as well as the degree of branching because the molar mass vs. elution volume curve and the conformation plot is not falsified in this technique. In addition, higher molar masses can be detected using HT-AF4 due to the absence of significant shear degradation in the channel. As a result the average molar masses obtained from AF4 are higher compared to SEC. The analysis time in AF4 is comparable to that of SEC but the adjustable cross-flow program allows the user to influence the separation efficiency which is not possible in SEC without a costly change of the whole column combination. (C) 2011 Elsevier B.V. All rights reserve
Keywords: Polyethylene; Polybutadiene; Polypropylene; Polystyrene; Field-flow fractionation; Light scattering; Size exclusion chromatography; Ultrahigh molar masses; Branching; Shear degradation